Antimicrobial and Wound Healing Activities of Local Euphorbia Hirta, Acalypha Indica and Phyllanthus Niruri - Ishak, Reezal (2004)
Herbal plants are well known for their capabilities in treating diseases for centuries. The World Health Organisation (WHO) has estimated that 80% of the world's population use botanical medicines for their primary health care needs. Some of the medicinal plants under the Euphorbiaceae family are Euphorbia hirta, Acalypha indica and Phyllanthus niruri. These plants are known as traditional remedy in many rural areas throughout the world and have been used for various purposes. This study focuses on the antimicrobial activity of aqueous and ethanol extracts of these plants against selected bacteria and fungi, and its wound healing properties on surgically incised mice. The antimicrobial test using the disc diffusion method at 20, 40 and 80 mglml extract-impregnated disc concentrations showed significant results (P<0.05) of Euphorbia hirta aqueous leaves and barks extracts against Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Salmonella enteritidis with inhibition zones ranged from 8.33 mm to 19.67 mm. The inhibition zones for Acalypha indica and Phyllanthus niruri aqueous leaves extracts were measured between 8.33 mm to 1 1.0 mm and 7.33 mm to 12.33 mm respectively, but no inhibition zones were seen with the bark extracts of both plants. Only the ethanol extracts of the leaves showed antibacterial activity. The results for Euphorbia hirta was the most significant (P<0.001) with inhibition zones ranging from 7.0 mm to 13.33 mm. Ethanol leaves extracts of Acalypha indica and Phyllanthus niruri had inhibition zones between 7.0 mm to 9.67 mm and 7.0 mm to 9.67 mm respectively. The results obtained showed comparable effects to commercial antibiotics of chloramphenicol, ampicilin, penicillin G, erythromycin, tetracycline and enrofloxacine as some of the plant extracts exhibit almost equal and even bigger inhibition zones. Antifungal activity were detected only with the Euphorbia hirta aqueous leaves extracts against Candida tropicalis with mean inhibition zones of 8.67 mm at 80 mglml discs concentrations. The aqueous extracts of the leaves were then tested for its wound healing properties on surgically incised mice. The extracts were applied topically over the incision and intlammatory and cicatrisation activities evaluated according to a designated scoring table. Acalypha indica showed the most significant results (Pc0.05) with better reduction of inflammation and increased cicatrisation activities on the wound compared to Euphorbia hirta and Phyllanthus niruri treated mice. In comparison to the acriflavine treated mice, the results demonstrated an equally good epithelial regeneration of the skins and showed to be better than the control group (no treatment).